Effect of the hyaluronic acid‐poloxamer hydrogel on skin‐wound healing: in vitro and in vivo studies. Issue 2 (30th April 2019) - Li, Xiaojuan; Li, Aimin; Feng, Fan; Jiang, Qiyu; Sun, Huiwei; Chai, Yantao; Yang, Ruichuang; Wang, Zhijie; Hou, Jun; Li, Ruisheng
Abstract: Background: Recent research into skin injury and wound healing has focused mainly on post‐trauma hemostasis, infection prevention, dermal regeneration and angiogenesis. However, less attention has been paid to air permeability and moisture loss prevention which also play important roles in injury healing. Methods: In the present work, we prepared a hyaluronic acid‐poloxamer (HA‐POL) hydrogel and tested the therapeutic effect of the hydrogel on skin‐wound healing. Results: The HA‐POL hydrogel transformed from sol to gel at 30°C, close to body temperature, and had stable moisturizing properties. HA‐POL hydrogel promoted skin‐wound healing and increased protein accumulation in the wound area. HA‐POL hydrogel allowed greater air permeability than Band‐aid, a typical wound covering. Results from transwell assays showed that the HA‐POL hydrogel effectively isolated skin‐wounds from bacterial invasion. Conclusion: This work demonstrates the advantages of using HA‐POL gel materials in the treatment of cutaneous wounds.